Bioaccumulation of zinc in edible tropical vegetables in Peninsular Malaysia and its human health risk assessment based on various ethnicities in Malaysia - Koe, Wei Wong; Yap, Chee Kong; Yaacob, Aziran; Nulit, Rosimah; Omar, Hishamuddin; Aris, Ahmad Zaharin; Sharifinia, Moslem; Bakhtiari, Alireza Riyahi; Al-Shami, Salman Abdo; Saleem, Muhammad; Okamura, Hideo (Springer, 2021)
Along with the growing utilization of zinc (Zn) and Zn-containing nanoparticles in various industries, Zn ecotoxicological evaluation on human food supply is necessary even though Zn is generally considered safe and rarely concentrated ecotoxicologically. This study aimed to investigate the bioaccumulation of Zn in 18 species of vegetables (seven leafy, nine fruity vegetables and one species each of tuber and legume) collected from two farming sites in the west coast of Peninsular Malaysia. A human health risk assessment (HHRA) was also conducted. In addition to HHRA based on the general population, HHRA based on each major ethnic group of the Malaysian society was also determined considering that the food consumption pattern would definitely be varied across ethnicities and age groups (children and adults). The study results showed that Zn concentrations were significantly higher (p < 0.05) in leafy vegetables than in other types of vegetables. However, the target hazard quotient (THQ) values were all found to be < 1.0. Therefore, based on the Malaysian ethnicities and age groups with their respective vegetable consumption patterns, the results indicated insignificant noncarcinogenic human health risk of Zn via oral consumption of vegetables by the Malaysian population. As a metric of measurement of HHRA, a comparison of THQ values could yield previously unreported insights into HHRA differences among the compared populations. A comparison of THQ values among the consumer groups indicated higher HHR for Chinese Malaysians and children due to their higher vegetable consumption and lower body weight, respectively. A comparison the Zn intakes of all the consumer groups with the recommended nutrient intakes indicated that the oral consumption of the vegetable species collected in this study would not result in Zn-related hazards and would not be able to fulfil the Zn dietary need of the individual consumer.